2017
DOI: 10.3382/ps/pew278
|View full text |Cite
|
Sign up to set email alerts
|

Blood biochemistry and immune response in Aseel chicken under free range, semi-intensive, and confinement rearing systems

Abstract: A study was conducted to investigate the effects of 3 different rearing systems [free range ( FR: ), semi-intensive ( SI: ), and confinement ( CF: )] on blood biochemical profile and immune response in 4 varieties of Aseel chicken [Lakha ( LK: ), Mushki ( MS: ), Peshawari ( PW: ) and Sindhi ( SN: )] for 10 wk duration (7 to 16 wk). At the age of 6 wk, in total, 180 cockerels were assigned to 12 treatment groups, 3 (rearing system) × 4 (Aseel chicken variety) factorial arrangement in 7 randomized complete block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 34 publications
7
31
0
Order By: Relevance
“…Our present study found that serum TP content was significantly improved by NRS, which may be linked with the lower exercise of birds under NRS because exercise can increase protein synthesis and result in total protein loss in blood (Rehman et al . ) and therefore was in accordance with decreased leg muscle and breast muscle percentage. High levels of TG and TC contents and low levels of HDL‐C content in serum are strongly associated with increased fat deposition (Zhang et al .…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Our present study found that serum TP content was significantly improved by NRS, which may be linked with the lower exercise of birds under NRS because exercise can increase protein synthesis and result in total protein loss in blood (Rehman et al . ) and therefore was in accordance with decreased leg muscle and breast muscle percentage. High levels of TG and TC contents and low levels of HDL‐C content in serum are strongly associated with increased fat deposition (Zhang et al .…”
Section: Discussionsupporting
confidence: 74%
“…A previous study in chickens reported that serum glucose and total protein contents were significantly improved by CRS compared to a free range system (Rehman et al . ). Sun et al .…”
Section: Discussionmentioning
confidence: 97%
“…A previous study had shown that the levels of glucose and plasma proteins under confinement rearing system were significantly higher than those under free‐range system (Rehman et al., ). Birds raised under FRS conditions have more exercise compared with those raised under CRS conditions, and exercise is known to induce the secretion of hormones, including insulin that can accelerate glucose metabolism in the blood (Rehman et al., ). In addition, birds raised in the CRS have higher levels of serum triglyceride and cholesterol and lower levels of HDL‐C than those raised in the FRS, which are all blood indicators that are closely related to fat deposition (Zhang, Luo, Yu, Chen,& Chen, ).…”
Section: Discussionmentioning
confidence: 94%
“…In the modern broiler industry, the increasing demand for higher chicken productivity and quality has stimulated innovations in rearing techniques, among which the rearing system has been identified as an important non‐genetic factor affecting broiler production and welfare (Li et al., ). Previous studies had reported that rearing systems played crucial roles in poultry production and quality (Michalczuk, Lukasiewicz, Zdanowska‐Sasiadek, & Niemiec, ; Rehman et al., ). The most widely and commonly used rearing systems are free‐range (FRS) and conventional cage‐rearing systems (CRS), and the chickens are raised under CRS conditions tending to show superior feed efficiency and growth performance (Wang et al., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation